Về áp dụng lý thuyết tập mờ trong mô hình quan hệ - Vương, Lê Tiến (Journal of Computer Science and Cybernetics, 2016)
In this paper we introduced a model of retrieval system based on the theory of fuzzy sets in which we constructed a suitable storage structure with incomplete inverted files (they contain even some incomplete inverted files for a collections of fuzzy data of database). On this concept, we introduced a method for fuzzy query processing in the system and shown some retrieval strategies. The general response system was also defined and the ability of these strategies was investigated.